Women, work and Islam: a Malaysian experience - Abd. Rokis, Rohaiza (IIUM Press, 2009)
Introduction: An activity when performed by men is often more highly valued than when performed by women [Pahl, 1984, Pearson, 2000]. Therefore, the objective of this chapter is to analyse the experience of female workers in their private lives. The relevant research questions are: Do employed women have a second shift at home? How do the feel at home......